Efektivitas Media PowerPoint dalam Promosi Kesehatan terhadap Pengetahuan, Sikap, dan Perilaku Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri - Fenni Rahmawati; Diani Octaviyanti Handajani; Rizka Esty Safriana; Siti Mudlikah (Universitas Muhammadiyah Gresik, 2026)
Background: Breast self-examination (BSE) is an important method for the early detection of breast cancer that should be introduced during adolescence. However, adolescent girls still demonstrate low levels of knowledge, attitudes, and practices regarding BSE. PowerPoint media can be utilized as an attractive and easily understandable health promotion tool. Objective: To analyze the effectiveness of PowerPoint media in improving knowledge, attitudes, and BSE practices among adolescent girls at MTs Nurul Jadid Randuboto. Methods: This study employed a true experimental design with a two-group pretest-posttest approach. The study population consisted of 58 female students in grades VII and VIII at MTs Nurul Jadid Randuboto. A total of 30 respondents were selected using random sampling and divided into intervention and control groups. The intervention was conducted through health promotion using PowerPoint media. Data were collected using questionnaires and observation checklists before and after the intervention. Data analysis was performed using the Mann–Whitney U test. Results: The findings demonstrated significant improvements in knowledge (p=0.000), attitudes (p=0.001), and BSE practices (p=0.002) among adolescent girls after receiving health promotion through PowerPoint media. Conclusion: PowerPoint media is effective as a health promotion tool for improving knowledge, attitudes, and BSE practices among adolescent girls